2011
DOI: 10.2337/dc10-1684
|View full text |Cite
|
Sign up to set email alerts
|

A Decrease in Glucose Variability Does Not Reduce Cardiovascular Event Rates in Type 2 Diabetic Patients After Acute Myocardial Infarction

Abstract: OBJECTIVETo assess the effect of intraday glucose variability (GV) on cardiovascular outcomes in a reanalysis of Hyperglycemia and Its Effect After Acute Myocardial Infarction on Cardiovascular Outcomes in Patients With Type 2 Diabetes Mellitus (HEART2D) study data.RESEARCH DESIGN AND METHODSType 2 diabetic patients after acute myocardial infarction were randomized to an insulin treatment strategy targeting postprandial (PRANDIAL; n = 557) or fasting/interprandial (BASAL; n = 558) hyperglycemia. GV was calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 11 publications
1
60
1
5
Order By: Relevance
“…Of note, previous reports suggested that acute oscillations of blood glucose have a more deleterious effect on endothelial function than constant hyperglycemia in patients with type 2 diabetes (T2DM) (3,4), which may support the concept that glycemic variability can induce oxidative stress and thereby affect the pathophysiologic pathways through which diabetes complications arise (5). However, although some studies have reported that increased glycemic variability may be associated with the incidence of diabetic retinopathy (6,7), diabetic neuropathy (8), and coronary artery calcification (9) in patients with T2DM and type 1 diabetes (T1DM), other studies have not supported this association (10)(11)(12). Nevertheless, although its relevance to vascular complications remains uncertain (13), at a given level of glycemia, increased glucose variability raises the risk of hypoglycemia (14)(15)(16) and, hence, is clinically important.…”
mentioning
confidence: 63%
“…Of note, previous reports suggested that acute oscillations of blood glucose have a more deleterious effect on endothelial function than constant hyperglycemia in patients with type 2 diabetes (T2DM) (3,4), which may support the concept that glycemic variability can induce oxidative stress and thereby affect the pathophysiologic pathways through which diabetes complications arise (5). However, although some studies have reported that increased glycemic variability may be associated with the incidence of diabetic retinopathy (6,7), diabetic neuropathy (8), and coronary artery calcification (9) in patients with T2DM and type 1 diabetes (T1DM), other studies have not supported this association (10)(11)(12). Nevertheless, although its relevance to vascular complications remains uncertain (13), at a given level of glycemia, increased glucose variability raises the risk of hypoglycemia (14)(15)(16) and, hence, is clinically important.…”
mentioning
confidence: 63%
“…The study was discontinued prematurely, however, due to too few CVD events and less-than-expected differences in postprandial glucose values. The HEART2D data were reanalyzed to evaluate if GV had an effect on cardiovascular outcomes (11). Only one of three markers of GV was reduced with the prandial-targeted therapy and this was the newest, least established GV marker.…”
Section: Dwilliam T Cefalu Editor In Chief Diabetes Carementioning
confidence: 99%
“…We are now blessed with a multiplicity of measures of glycemic variability. These include SD, coefficient of variation (CV), interquartile range, MAGE, MODD, mean absolute glucose (MAG) change per hour, and several subtypes of the SD, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] including total SD (SD T ), SD within days (SD w ), between daily means (SD dm ), between days (SD b ), between days after correction for variability in daily means (SD b // dm ), variability by time of day for the mean glucose profile from several days (SD hh:mm ), measures of the stability of the glycemic profile or similarity of glucose patterns from day to day (root mean square error), [17][18][19] a "distance travelled" 20 that is closely related to the MAG rate of change, 21 glucose fluctuation as defined by Mori and associates, 22 and combinations of several of these measures. 11,19,23 Workers in the field need some time to evaluate and compare the performance of the various measures that have been proposed.…”
Section: The Magnitude Of Glycemic Variability Is Highlymentioning
confidence: 99%